Vascular hyporeactivity to angiotensin II and noradrenaline in a rabbit model of obesity - Jerez, Susana Josefina (2012)
This study was conducted to explore the vascular reactivity of angiotensin II and noradrenaline and their relationship with endothelial function in rabbits fed a high-fat diet (HFD). The animals were fed either an HFD or regular chow [control diet (CD)]. After 12 weeks, the rabbits fed the HFD showed higher blood pressure, body weight, and insulin levels. Glucose tolerance was impaired and positively related to blood pressure. An endothelium-independent decrease of the sensitivity to angiotensin II [pD 2 endothelium-intact aortic rings (E+) in CD: 8.02 ± 0.07 vs. HFD: 7.60 ± 0.01; pD 2 endothelium-removed aortic rings (E-) in CD: 8.16 ± 0.11 vs. HFD: 7.83 ± 0.16] and noradrenaline (pD 2 E+ in CD: 6.36 ± 0.06 vs. HFD: 5.29 ± 0.06; pD 2 E- in CD: 6.11 ± 0.08 vs. HFD: 5.80 ± 0.08) was found. Noradrenaline desensitized the angiotensin II response (pD 2 with noradrenaline pretreatment in E+: 7.03 ± 0.16; in E-: 7.10 ± 0.02), but angiotensin II did not change the noradrenaline response. Acetylcholine maximal relaxation and basal nitric oxide (NO) release were comparable in both diet groups. The efficacy of angiotensin II (R max CD: 4604 ± 574 mg vs. HFD: 3251 ± 533 mg) and noradrenaline (R max CD: 11,675 ± 804 mg vs. HFD: 7975 ± 960 mg) was reduced in E+. L-N G-nitroarginine methyl ester (L-NAME) recovered the efficacy of noradrenaline (R max L-NAME: 12,015 ± 317 mg). In contrast, L-NAME had no effect on the angiotensin II response. Noradrenaline enhanced NO levels, but angiotensin II did not. Therefore, NO was associated with hyporeactivity to noradrenaline. The resting potential was more negative in E+, and the endothelium diminished the angiotensin II-induced depolarization. These findings demonstrated that the crosstalk and the endothelium may induce hyporeactivity to angiotensin II and noradrenaline as a mechanism to compensate the increase in the blood pressure in HFD-induced obesity.